Estrategias Pedagógicas Para Desarrollar La Conciencia Corporal y Fortalecer Habilidades Artísticas en los Estudiantes de Grado Once del Colegio Distrital la Amistad de La Jornada Mañana a Través del Montaje Tuna Papita del Grupo Kjarkas. (2018)
The topic of this thesis is: pedagogical strategies to develop body awareness and strengthen artistic skills in eleventh grade students of the La Amistad District School of the morning session through the montage Tuna papita by the Kjarkas group, the idea was born after applying some concentration and creativity exercises; a staging based on myths and legends in which students had to act and create steps according to a specific melody. These exercises revealed deficiencies in concentration and lack of consciousness and body expression. These factors are important because they develop sensitivity, communication, imagination and creativity. According to Letra, Ruano & Sierra, (2006), it also contributes to strengthening some of the soft skills that companies most seek in their employees, such as being a good communicator and having an assertive body and facial expression. For these students who are in their last year of school, it is important to strengthen these skills since they will allow them to perform better in the workplace.